Design and Development of Solar Powered Brown Rice Milling Machine - kluay-on, pawarit; Kalsirisilp, Roongruang; Langapin, Jaturong (Srinakharinwirot University Engineering Journal, 2023)
This research project aims to design and develop a solar powered brown rice milling machine. Solar powered brown rice milling machine consists of five main structures: 1. solar panel 2. battery 3. inverter set 4. charger 5. brown rice milling machine with five rubber rolls. The motor speeds were set to 1,300, 1,400, and 1,500 rpm. The clearance between the cylinders was set at 0.8, 0.9, and 1.0 mm. Three varieties of paddy namely Thai jasmine rice, Pathum Thani rice and jasmine 85 rice. The moisture content of paddy in the range between 13-15 percent (wet basis) was used in this study. The performance parameters investigated were machine capacity, percentage of broken rice and husking index. The research study was conducted based on Thai Industrial Standards 888-2532. The machine performance test for Thai jasmine rice revealed that the optimum speed and clearance between cylinders were 1,400 rpm and 0.9 mm, respectively. The machine capacity was 17.25 kg of rice per hour. The broken rice was 0.46%, respectively. The machine husking index was determined to be 96.85%. For Pathum Thani and jasmine 85 rice, the optimum revolution speed of motor and clearance between cylinders were 1,500 rpm and 0.9 mm, respectively. The machine capacity was 25.01 and 21.51 kg of rice per hour for Pathum Thani and jasmine 85 rice, respectively. The machine husking index was determined to be 96.87 and 96.87%, respectively. Based on the analysis of engineering economics, it was found that the rice milling machine worked 2,400 hours per year, with an average cost of 1.68 baht per kilogram. The break-even point of the machine was 337 hours per year with a payback period of 0.62 years.